Activities of the Public Health Section of the National Administration for the Territory of Banat, Backa and Baranja on Improvement of Public Health - Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
National Administration for the territory of  Banat, Backa and Baranja was established at the Great National Assembly, which was held in Novi Sad in November 1918. On the same occasion the Great National Council was established as legislative authority in the territory of Vojvodina. National Administration was an authority of executive power and was divided into 11 sections. Each section had jurisdiction in different matters. One of them was Section of Public Health. Activities of the Section of Public Health had great significance and were aimed at improvement of health care system in the territory of Vojvodina. In the insecure circumstances immediately after the World War I, Section of Public Health spared no effort in order to establish normal functioning in hospitals and to stem the flow of various infectious diseases in the territory under its power. Measures that Section of Public Health had undertaken, laid the good foundations for establishing new health care system within the Kingdom of Serbs, Croats and Slovenes. Based on data from archives from relevant funds in the Archives of Vojvodina, some of the activities of the Section of the Public Health are presented in the paper.